Pengaruh Pelatihan Komunikasi Interpersonal terhadap Peningkatan Kualitas Hubungan Sosial Mahasiswa Baru - Eva Palupi (IAIN Kudus, 2019)
Eventhough it is said that men was a perfect human being, men also has limitation. People everywhere develop social interaction to satisfy their need for affections and completed their limitation. Social relation in the first-year college sudents plays as a crusial part because its has importance impacts to students success and well-being. Many studies has proved that quality of social relationship can be improved through interpersonal communication. The purpose of this study was to investigate the effectiveness of an interpersonal communication skill training to improve quality of social relationship among first-year students of IAIN Salatiga. This study was quasi-experimental. The number of participant in the experiment group were 21 (7 male and 14 female) and 20 (9 male and 11 female) in control group. Finding showed that interpersonal communication skill training increased the quality of interpersonal relashionship among first-year students of IAIN Salatiga significantly. There’s a difference quality of interpersonal relationship score after the treatment, that experiment group has higher score than control group’s (t = 2.30, p < 0.05).